Analyzing CSR and GCG Impact on Financial Performance through Intellectual Capital: A Literature Review - Nursabila, Kiki Rohmatus; Kusumaningtias, Rohmawati (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study uses intellectual capital as a mediating variable to examine how corporate social responsibility (CSR) and good corporate governance (GCG) affect a company’s financial performance. This study examines numerous empirical studies produced between 2020 and 2025 using a literature review methodology. The study’s findings demonstrate that GCG and CSR both directly and indirectly improve financial performance through Intellectual Capital (IC). Effective CSR can strengthen trust and corporate image. Good governance can improve the efficiency and transparency of corporate management. Meanwhile, IC can transform social and governance practices into competitive advantages. In general, a company’s financial performance can be enhanced by integrating CSR, GCG, and IC. To get comprehensive results, more research is advised to empirically investigate the mediation of IC in the relationship between CSR and GCG on financial performance